Enthalpy of collagen interfibrillar bonds in fetal membranes. (20th September 2021) - Marom, Y.; Gengrinovitch, S.; Shalev, E.; Shilo, D.
Graphical abstract: Abstract: During pregnancy, the fetal membrane (FM) is subjected to mechanical stretching that may result in preterm labor. The structural integrity of the FM is maintained by its collagenous layer. The disconnection and reconnection of molecular bonds between collagen fibrils are the fundamental processes that govern the irreversible mechanical and supermolecular changes in the FM. Here, we study the activation enthalpy of interfibrillar bonds in ex-vivo human FM. We analyze the strain-rate and temperature dependence of the irreversible deformations in FM subjected to inflation tests, which apply mechanical conditions similar to those experienced by the FM prior to and during the initiation of labor contractions. The obtained activation enthalpy of interfibrillar bonds matches the typical enthalpy values of polyvalent ionic bonds, implying on another important role that ions like Ca and Mg may play in the gestation and labor.